Histological Study for Skin of Horse - Ali Khudheyer Obayes (Tikrit Journal of Pure Science, 2023)
The present study was done on skin of horse,samples are taken from six animals after  anaesthetized the animals and slaughttered . Samples are taken from dorsal back area ,the collected tissues were fixed in 10% formalin for 24 hrs. tissue was prepared for light microscopic examination . the  result showed skin of horse  composed of  Epidermis & dermis .epidermis are keratinized stratified squamous epithelium ,that divided into four cellular layers  from the top (stratum corneum ,granulosum ,spinosum and basale), stratum basale are consist of simple cubiodal epithelium cells were rest on the basement membrane, Melanocytes cells are located in stratum basale .Dermis composed of  papillary layer and dermal papilla. Papillary  layer composed of bundles of collagenouse fibers with fibroblast. Primary hair follicles. primary hair follicle which surrounded by sweat glads and sebaceous glands. sweat glands was simple tubular gland which lined by simple cuboidal epithelium, the alveoli of sweat gland that surrounded by Myoepithelial cells. Sebeceous gland, Like double saccule, lined by simple cubiodal epithelium cells that contain fat dropletes. Primary hair follicle, that consist of Hair shaft in the center which represented the medulla, it was enclosed by cortical layer of stratified squamous epithelium.The primary & secondary hair follicle were attached to the smooth muscle bundles, was represented the arector pilli  muscles. Small artery near the hair follicle that supply the oxygen and nutrient to the skin.